Evaluasi Usability pada E-Learning Menggunakan Metode Human Centered Design dan Usability Testing One Click Service SMK PGRI 3 Malang - Erfan Yuono; Satrio Hadi Wijoyo; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
SMK PGRI 3 Malang is one of the vocational vocational high schools that has utilized information technology in its learning and learning activities. The LMS One Click Service that was developed is often used by students to view data from educators, see the results of learning scores, and thefeature online drive that is very often used by students. From the data collected by researchers on students by conducting interviews, there are still problems with the application of thisLMS One Click Servic . The problems found were on thefeatures website One Click Service, among others, lack of detailed menu explanation, untidy button placement, and lack of explanation on the menu, the content displayed on themenu is one drive still one, thus hindering student performance. In this study, the authors used themethod Human Ceneterd Design for makingproposals design interface, and themethod Usability Testing for evaluating the design proposed interface. The success parameters are divided into 3 aspects, namely the aspects of efficiency, effectiveness, and satisfaction. The results of the test using the efficiency aspect, the effectiveness aspect, and the satisfaction aspect are as follows, the efficiency aspect increased by 36%, the effectiveness aspect was divided into 3 aspects, the success aspect got an average of 67.2%, Non Critical Error 23.3 % and Critical Error of 9%. Then on the satisfaction aspect, it gets a score of 81.5 with thecategory Acceptable